Hubungan Psychological Capital dengan Work Engagement pada Guru SMA Negeri Di Kabupaten Tanah Datar - Aliyah Rahman; Tuti Rahmi (Science and Education Journal (SICEDU), 2026)
This study aims to examine the relationship between Psychological Capital and Work Engagement among public senior high school teachers in Tanah Datar Regency. This research employed a quantitative approach with a correlational design. The participants consisted of 233 teachers selected using cluster sampling technique. Data were collected using the Psychological Capital Questionnaire (PCQ) and the Utrecht Work Engagement Scale (UWES), and were analyzed using Pearson correlation with the assistance of JASP version 0.19.3. The results indicated a positive and significant relationship between Psychological Capital and Work Engagement. Individuals with more positive psychological conditions tend to have higher levels of work engagement, characterized by energy, dedication, and involvement in their work. These findings highlight the importance of developing Psychological Capital as an effort to enhance teachers’ Work Engagement.